2013
DOI: 10.5897/ajar12.1576
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility capability classification (FCC) for rice production in Cameroon lowlands

Abstract: Fertility capability classification (FCC) system is a technical soil classification system focusing quantitatively on physical and chemical properties of soil important to soil fertility management. Lowland rice cultivation is a major activity in Cameroon, where demand for the commodity is increasing amidst increasing production constraints. This study was intended to classify lowland rice soils in major rice-growing areas into fertility capability classes, identify soil fertility limitations to increased lowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Pedon MISSE-P1 had higher content of available P in the topsoil than pedons MARU-P1 and BIHA-P1 which had low levels throughout their profile depths. Some researchers elsewhere [83,9] reported similar trend. The low available P in pedons MARU-P1 and BIHA-P1 may be attributed to low inherent P in their parent materials which developed mainly on basement rocks of granite, quartzite and shale [63,30,16] and due to the effects of low soil pH which normally favours P fixation [66,16].…”
Section: Available Phosphorus and Exchangeable Basessupporting
confidence: 71%
See 1 more Smart Citation
“…Pedon MISSE-P1 had higher content of available P in the topsoil than pedons MARU-P1 and BIHA-P1 which had low levels throughout their profile depths. Some researchers elsewhere [83,9] reported similar trend. The low available P in pedons MARU-P1 and BIHA-P1 may be attributed to low inherent P in their parent materials which developed mainly on basement rocks of granite, quartzite and shale [63,30,16] and due to the effects of low soil pH which normally favours P fixation [66,16].…”
Section: Available Phosphorus and Exchangeable Basessupporting
confidence: 71%
“…The low available P in pedons MARU-P1 and BIHA-P1 may be attributed to low inherent P in their parent materials which developed mainly on basement rocks of granite, quartzite and shale [63,30,16] and due to the effects of low soil pH which normally favours P fixation [66,16]. The fixation process involves reaction of P with iron (Fe) and aluminum (Al) thereby inhibiting availability of P into the soil for plant uptake [53,83,66,9]. [53] reported that available P of < 15 mg kg -1 in soils would show crop response to P as observed in pedons MARU-P1 and BIHA-P1.…”
Section: Available Phosphorus and Exchangeable Basesmentioning
confidence: 99%
“…The low to medium levels of extractable P in the fields in Bukoba and Biharamulo Districts may be attributed to the low inherent P in the parent materials developed mainly on basement rocks of granite, quartzite and shale [51,13,45]. It may also be due to low soil pH that normally favours reaction with iron (Fe) and aluminium (Al) to inhibit the availability of P into the soil for plant uptake due to P fixation [36,52,17,45,53]. According to [36], plant response to applied P could be expected when soil available P is less than 15 mg kg -1 soil.…”
Section: Extractable Phosphorus and Sulphurmentioning
confidence: 99%
“…The decline in soil fertility had been attributed to inadequate use of fertility inputs, on-going soil degradation, and increasingly intense land use without organic and mineral inputs to improve on soil fertility by burgeoning populations (St. Clair and Lynch, 2011). The rising temperature, drought, intense precipitation and other adverse weather conditions occasioned by the prevailing climate change could worsening the decline of soil fertility in the tropics (St. Clair and Lynch, 2011; Tabi et al 2013).…”
Section: Introductionmentioning
confidence: 99%